2014
DOI: 10.2464/jilm.64.93
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dillamore orientation during accumulative roll bonding of {001}^|^lang;100^|^rang; aluminum single crystal

Abstract: A {001} 100 oriented aluminum single crystal was deformed by nine cycles of accumulative roll bonding which corresponded to a total equivalent strain of ε=7.2. The formation of {4 4 11} 11 11 8 component in deformation texture was examined by using electron back-scatter diffraction method. The specimen processed by five cycles ARB (ε=4) developed four variants of {123} 634 orientation in the deformation texture. Between the five and nine cycles, the four variants of {123} 634 rotated toward {4 4 11} 11 11 8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…8) The area fraction of {001} ©110ª was 5.8% in the (213) (001) [100] single crystal, the crystal rotation from {001} ©110ª to D orientation hardly occurred. Thus, the formation of {001} ©110ª (or {116} ©331ª) orientation, especially when formed in the surface layer, is important for the occurrence of cyclic ratcheting, which depends on the initial crystal orientations.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…8) The area fraction of {001} ©110ª was 5.8% in the (213) (001) [100] single crystal, the crystal rotation from {001} ©110ª to D orientation hardly occurred. Thus, the formation of {001} ©110ª (or {116} ©331ª) orientation, especially when formed in the surface layer, is important for the occurrence of cyclic ratcheting, which depends on the initial crystal orientations.…”
Section: )mentioning
confidence: 99%
“…In our previous studies, 7,8) (112) [11 1] and (001) [100] oriented aluminum single crystals were deformed up to a total reduction in thickness of 99.8% (an equivalent strain of 7.18) by conventional rolling and subsequent ARB. Both single crystals indicated that the resultant main texture components in the center layer were D {4 4 11} ©11 11 8ª orientation (Dillamore orientation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic deformation induced crystallographic texture has been a subject of research for decades because of its consequences for the material properties and deformation behaviours [1][2][3]. Among the texture components, Cube {0 0 1}<1 0 0> is an considerably investigated orientation in FCC structured metals (e.g., [4][5][6][7][8][9][10][11][12][13][14]). It is accepted that this orientation is unstable under rolling or plane strain compression (PSC) process [4][5][6], since it locates in the 'divergent' region of Euler space.…”
Section: Introductionmentioning
confidence: 99%
“…For single crystal after a ~50% thickness reduction, crystallographic orientations mainly rotate about transverse direction (TD) for exact Cube [4,7,8] and also for the initial orientation rotated about TD by 5° (5TD) [9], but the rotation axis is not specific for initially spined around rolling direction (RD) at 5° (5RD) [10]. A small deviation angle of 1.5° led to an asymmetrical distribution of texture after a large reduction [11,12]. Small deviation angles in single crystals were chosen intendedly to study the stability of Cube orientation during deformation in Refs.…”
Section: Introductionmentioning
confidence: 99%